REFORMATION OF NUCLEOLUS-LIKE BODIES IN THE ABSENCE OF POSTMITOTIC RNA SYNTHESIS - Stevens, A. R. (The Rockefeller University Press, 1971)
The dependence of nucleolar reformation on RNA synthesis that resumes in late anaphase or early telophase has been investigated in synchronously dividing Amoeba proteus. RNA synthesis was completely inhibited throughout all stages of mitosis and the early hours of interphase with high concentrations of actinomycin D. In such cells, nucleolus-like bodies that bind azure B and pyronin were apparent in the reformed nuclei. The bodies appear as dense, fibrous masses with loosely associated, finely fibrillar material. There are no characteristic granular regions in the reformed structures. It is suggested that the bodies probably represent mainly nucleolar protein and residual RNA which can bring about the reorganization of nucleoli in the absence of postmitotic RNA synthesis.